Musculoskeletal asymmetries in adolescent fencers: developmental adaptations and injury implications – a narrative review - Wisoky, Wiktor; Czapla, Natalia; Strużyńska, Ewelina; Ziółkowska, Weronika; Łopińska, Joanna; Majchrzycka, Marta; Graczyk, Martyna; Ignyś, Piotr; Graczyk, Natalia; Majchrzak, Mateusz (Quality in Sport, 2026)
Introduction: Fencing is an asymmetric sport, that combined with a dynamic development in young athletes can contribute to some functional imbalances especially in the musculoskeletal system. In young athletes, one-sided training loads can worsen physiological asymmetries associated with growth and puberty, potentially increasing the risk of overload injuries. Aim of the study: The aim of this narrative review was to analyse the available literature on the nature of musculoskeletal asymmetries in fencers during their developmental years, their relationship to maturation processes, and potential injury implications. Methods: A review of publications from 2000 to 2025 was conducted using PubMed, Scopus, Web of Science and SPORTDiscus databases. Studies on the population aged 10–18 and works related to biomechanics, biological maturation and injuries in asymmetrical sports, with particular emphasis on fencing, were included. Results: The available data indicate that young fencers exhibit asymmetries in muscle strength, range of motion and body segment alignment, especially in the lower limbs, shoulder girdle and spine. Small differences may determine a functional adaptation to the specifics of the discipline, but their intensity during the pubertal growth speed may increase the risk of overload injuries, including knee and lower back pain. The limited number of extensive studies makes it difficult to clearly determine cause-and-effect relationships. Conclusions: Musculoskeletal asymmetries in young fencers are an adaptive-pathological phenomenon, depending on the stage of biological development and the training load. Early observation of functional parameters and the implementation of correct training should be an integral part of injury prevention in this population.